RELEVANSI KURIKULUM PJKR-FIK-UNY TAHUN2002 TERHADAP KURIKULUM BERBASIS KOMPETENSI PENDIDIKAN JASMANI TAHUN 2004 - - Sridadi (Jurnal Pendidikan Jasmani Indonesia, 2006)
Curriculum is important component in education and learning process. Every educationpractice always refer to the current curriculum, in order to have clear goals and direction oneducation. On the fast changing world of globalization and challenges that follow, there is aneed to create an education that fit with the needs of current situation. Depdiknas has cometo the answer by planning and formulating a set of reference tools for educational practiceto develop every aspects of education which include knowledge, skill, and attitude. This hasbeen implemented in every stage and type of education. This tool is known as competencebased curriculum or Kurikulum Berbasis Kompetensi (KBK). Competence basedcurriculum in 2004 has been officially become reference to every formal education practicestarting from elementary education until high education. This curriculum consists of basicframework of 2004 curriculum, standard learning materials and standard subject mattercompetence which all is arranged on each subject on each education unit. According to2004 curriculum, improvement effort of this curriculum is aim to increase quality andrelevance education that has to be done in a comprehensive way. Referring on theimplementation of competence based curriculum on 2004, PJKR-FIK-UNY programmestudy as the institution to create educational experts should start to organize, assess andevaluate itself. Question raised is that curriculum of 2002 that are currently being use byPhysical Science Faculty, especially programme study PJKR, still relevant with the currentsituation? Is the goal, content and material on the curriculum can help students to face thefree competency on the education? Is the material and content in 2002 curriculum (PJKR)still relevant with the need of community?Keywords: relevance, competence based curriculum, physical education.